Mechanical properties and engineering application of cellulose fiber-reinforced concrete. (March 2020) - Ma, Weili; Qin, Yuan; Li, Yanlong; Chai, Junrui; Zhang, Xianwei; Ma, Yingbiao; Liu, Haimin
Highlights: The physical parameters, failure modes, and mechanical properties of CFRC are studied. Mechanical test results of different fiber contents of CFRC are compared. CFRC is applied at the Nazixia Hydropower Station. Abstract: The inclusion of fibers in concrete slabs improves the concrete's mechanical properties. In this work, the mechanical properties of cellulose fiber (CF)-reinforced concrete (CFRC) with four fiber contents (0.6, 0.9, 1.2, and 1.5 kg/cm 3 ) are determined for application at the Nazixia Hydropower Station. The mix design ratio of plain concrete (PC) is 1:0.47:2.74:5.09 (cement:water:sand:aggregate), with a water–cement ratio of 0.47. Some parameters of the CFRC, including strength, energy absorption capacity, and toughness, are compared and analyzed through mechanical tests. The compressive, splitting tensile, and flexural strengths of the CFRC are higher than those of PC, especially the concrete with 0.9 kg/m 3 fiber content. The concrete with the best fiber content in the test (0.9 kg/cm 3 ) is applied to the Nazixia face slab. In addition, the service period of the dam face slab is monitored, and changes in the temperature, stress, and strain of the CFRC face slab are analyzed from July 2013 to January 2018. Results show that adding CF to the face slab concrete improves the performance of the face slab concrete by enabling it to maintain a stable working state in cold climates and during earthquakes. Thus, CFRC is suitable for concrete slabs in extreme environments.